Biogeography of Mesalina (Reptilia: Lacertidae), with special emphasis on the Mesalina adramitana group from Arabia and the Socotra Archipelago - Simó-Riudalbas, Marc; Tamar, Karin; Šmíd, Jiří; Mitsi, Pelagia; Sindaco, Roberto; Chirio, Laurent; Carranza, Salvador (Molecular phylogenetics and evolution, 2019)
The lacertid lizards of the genus Mesalina inhabit the arid regions of the Old World, from North Africa to NW India. Of the 19 recognized species within the genus, eleven occur in Arabia. In this study, we explore the genetic variability and phylogeographic patterns of the less studied M. adramitana group from southern Arabia and the Socotra Archipelago within the phylogenetic and biogeographic context of the entire genus. Our unprecedented sampling extends the distribution ranges of most Mesalina species and, for the first time, sequences of M. ayunensis are included in a phylogenetic analysis. We perform analyses of concatenated multilocus datasets and species trees, conduct species delimitation analyses, and estimate divergence times within a biogeographic framework. Additionally, we inferred the environmental suitability and identified dispersal corridors through which gene flow is enabled within M. adramitana. Our results show that the Socotra Archipelago was colonized approximately 7 Mya by a single oversea colonization from mainland Arabia. Then, an intra-archipelago dispersal event that occurred approximately 5 Mya resulted in the speciation between M. balfouri, endemic to Socotra, Samha and Darsa Islands, and M. kuri, endemic to Abd al Kuri Island. Similar to previous studies, we uncovered high levels of genetic diversity within the M. adramitana species-group, with two highly divergent lineages of M. adramitana living in allopatry and adapted to locally specific climatic conditions that necessitate further investigation.
Keywords: Base Sequence; ještěři; ekosystém; Arabian Peninsula; Africa, Northern; Genetic Variation; Arábie; Ecosystem; Land bridge; Speciation; fylogeneze; Phylogeography; Time Factors; Lacertids; sekvence nukleotidů; severní Afrika; ostrovy; Arabia; fylogeografie; Endemicity; Models, Biological; biologické modely; migrace zvířat; genetická variace; Animals; Islands; Animal Migration; zvířata; Allopatry; mitochondriální DNA; Lizards; Phylogeny; Niche modelling; časové faktory; DNA, Mitochondrial